Water quality in agriculture: risks and risk mitigation - Drechsel, Pay; Marjani Zadeh, S.; Salcedo, F. P. (Food and Agriculture Organization of the United Nations, 2023)
This publication, Water Quality in Agriculture: Risks and Risk Mitigation, emphasizes technical solutions and good agricultural practices, including risk mitigation measures suitable for the contexts of differently resourced institutions working in rural as well as urban and peri-urban settings in low- and middle-income countries. With a focus on sustainability of the overall land use system, the guidelines also cover possible downstream impacts of farm-level decisions. As each country has a range of site-specific conditions related to climate, soil and water quality, crop type and variety, as well as management options, subnational adjustments to the presented guidelines are recommended. Water Quality in Agriculture: Risks and Risk Mitigation, is intended for use by national and subnational governmental authorities, farm and project managers, extension officers, consultants and engineers to evaluate water quality data, and identify potential problems and solutions related to water quality. The presented guidelines will also be of value to the scientific research community and university students.